2012
DOI: 10.1182/blood-2012-01-405332
|View full text |Cite
|
Sign up to set email alerts
|

Loss of p53 accelerates the complications of myelodysplastic syndrome in a NUP98-HOXD13–driven mouse model

Abstract: The nucleoporin gene NUP98 is fused to several genes including HOXD13 in patients with myelodysplastic syndromes (MDS), acute myeloid leukemia, and chronic myeloid leukemia, blast crisis. Genetically engineered mice that express a NUP98-HOXD13 (NHD13) transgene (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 34 publications
4
24
0
Order By: Relevance
“…Similar to the previous study, 18 we observed a shortened lifespan in NHD13 mice lacking p53, with a median survival of 95 days compared with 126 days in p53-deficient mice alone (Po0.01) and 353 days in NHD13 mice alone Distinct roles for P53 and PUMA in myelodysplasia AA Guirguis et al…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Similar to the previous study, 18 we observed a shortened lifespan in NHD13 mice lacking p53, with a median survival of 95 days compared with 126 days in p53-deficient mice alone (Po0.01) and 353 days in NHD13 mice alone Distinct roles for P53 and PUMA in myelodysplasia AA Guirguis et al…”
Section: Resultssupporting
confidence: 89%
“…17 To define the hematopoietic subsets affected by apoptosis in NHD13 mice, we measured the numbers and percentages of cells undergoing apoptosis among defined hematopoietic stem and progenitor cells by flow cytometry. As previously reported, 18,19 the proportions of Lineage neg Sca-1 + c-Kit + (LSK) stem/multi-potent progenitor cells and Lineage neg Sca-1 − c-Kit + (LK) progenitor cells were reduced approximately three-fold and two-fold, respectively (Figure 1a). Using the Signaling Lymphocyte Activation Molecules (SLAM) CD48 and CD150, we found that longterm (LT)-HSCs (LSK,CD150 + CD48 − ) and short-term (ST)-HSCs (LSK, CD150 − CD48 − ) were more markedly reduced (410-fold) in proportion and absolute numbers than multipotent progenitors, MPP (LSKCD150 − CD48 + ) (Figures 1a and b).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations